1997
DOI: 10.1039/a604694k
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-doped bismuth vanadate solid electrolytes

Abstract: Part 1.-Synthesis and characterization of Bi , (0.1∏x∏0.25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…Table 4 summarises the refined structural parameters; the R factors of weighted pattern (R wp ), pattern (R p ) and Bragg (R B ) converge to 16.1 %, 12.9 % and 5.87 % respectively. These values agree with those obtained in other Aurivillius [19,20] and Sillén-Aurivillius [8] phases. It is worth mentioning that the high B value obtained for Bi (2) in the refinement agrees with our previous work on the isostructural Bi 4 Ti 1/2 W 1/2 O 8 Cl compound.…”
Section: Average Structure: Powder X-ray Diffraction Refinementsupporting
confidence: 94%
“…Table 4 summarises the refined structural parameters; the R factors of weighted pattern (R wp ), pattern (R p ) and Bragg (R B ) converge to 16.1 %, 12.9 % and 5.87 % respectively. These values agree with those obtained in other Aurivillius [19,20] and Sillén-Aurivillius [8] phases. It is worth mentioning that the high B value obtained for Bi (2) in the refinement agrees with our previous work on the isostructural Bi 4 Ti 1/2 W 1/2 O 8 Cl compound.…”
Section: Average Structure: Powder X-ray Diffraction Refinementsupporting
confidence: 94%
“…Nonetheless, Adler et al have used wideline and relaxation studies of oxygen mobility to estimate O 2vacancy trapping energies and to investigate O 2mobility at elevated temperatures (6,7). Here, we extend our previously developed methodology for fluoride systems (8,9) and report detailed 17 (1,(13)(14)(15)(16). These materials can be used as oxygen separation membranes at moderate temperatures (430°to 600°C) (2).…”
mentioning
confidence: 88%
“…In addition, subtle differences in the Raman and infrared spectra (12,13) have been accepted as indicating only minor variations of the more general LDA structural category, and similar claims have been made regarding the HDA category (7). Structural studies by neutron and x-ray diffraction (14)(15)(16)(17)(18) have also resulted in the suggestion that liquid water can be considered a mixture of the low-and high-density forms (5). Conversely, relaxation, as indicated by the shift in the first diffraction peak in the HDA form of D 2 O upon annealing, has also resulted in the suggestion that some variation in the HDA structure may exist (7).…”
mentioning
confidence: 97%
“…Substitution with Mn 2+ in the bismuth vanadate has not been determined earlier, however study with Mn 4+ reducing under different experimental conditions is reported [11,12]. To be more detailed on this substitution, Bi 4 V 2−x Mn x O 11−δ compounds were synthesized in the composition range (0≤ x≤0.4), characterized with X-ray diffraction study and electrical conductivity measurement.…”
Section: Introductionmentioning
confidence: 99%